Mini-DNA barcoding for the identification of commercial fish sold in the markets along the Taiwan Strait. (June 2020) - Xing, Bingpeng; Zhang, Zhilan; Sun, Rouxin; Wang, Yanguo; Lin, Mao; Wang, Chunguang
Abstract: The detection of fish species substitution and fraud has become an important topic in the food industry, and there is a growing need for reliable, rapid, and reproducible tests to identify commercial fish. The most accredited morphological method is not simple and cannot be used for processed products. Full length DNA barcodes can partly solve this problem but also failed in highly processed products because of the DNA degradation. This study aims at test mini-DNA barcoding for the identification of commercial fish and processed products on the market along Taiwan Strait. 355 sequences were obtained from 365 fish samples which identified to 12 orders, 38 families, 66 genera, and 86 species. The substitution rate was 21.97% of the total. The average Kimura-2-parameter (K2P) distances within species, genera, families and orders were 0.37%、18.10%、22.10% and 25.40%, respectively. The mean interspecific distance was 49-fold higher than the mean intraspecific distance. The K2P neighbor-joining trees based on the sequence generally clustered species in accordance with their taxonomic classifications. This study demonstrated the mini-DNA barcode was reliable and effective for fish authentication monitoring and could be used by surveillance authorities in the quality control of processed fish products, towards ensuring consumer rights. Highlights: Mini-DNA barcodes can be amplified from fish and processed products contain degraded DNA. Mini-DNA barcodes have sufficient sequence variation and divergence to indentify the fish species. The mean interspecific distance is 49-fold higher than the intraspecific in mini-DNA barcoding of samples. Mini-DNA barcoding is effective in the recognition of commercial fish and processed products.